Analisis Komparatif Pendapatan Petani Pelaksana Pengelolaan Tanaman Terpadu Padi Sawah dengan Petani Non Pelaksana Pengelolaan Tanaman Terpadu Padi Sawah di Desa Pugaan Kecamatan Pugaan Kabupaten Tabalong - Azwar Saihani; As’ari As’ari (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This is research result with aim to for the cost analysis of, acceptance and comparison of earnings of farmer of executor of manajement of inwrought crop (PTT) by execute management of inwrought crop of rice field paddy. This research is executed by in Countryside of Pugaan Sub-Province of Tabalong. Election of farmer of sampel by purposive counted 23 people for the farmer of executor of PTT rice field paddy and by random sampling counted 23 people for farmer oflis non executor of PTT rice field paddy. Data which used in this research in the form of primary data and data of sekunder collected with interview technique, and record-keeping of survey. Management of inwrought crop ( Paddy rice field PTT ) are new innovation to solve various problem of improvement of paddy crop productivity. Result of analysis of that flattening to flatten in one hectare is expense of for the executor of PTT Rp. 20.046.618,45 and to the non executor of PTT Rp. 16.641.386,9, while result produce Rp. 22. 638.000 and Rp. 17.801.640,85. Earnings for the farmer of executor of PTT is Rp. 17.232.171,05 in one hectare, for farmer of non executor of PTT is Rp. 12.755.601,16 in one hectare. Of the analysis result concluded that flattening to flatten in one hectare of expense of, acceptance and earnings of farmer of executor of higher PTT than farmer of non executor of PTT